Synthesis of NIO/SnO2 Nanocomposite for Applied as Light Sensitive Electrodes - Zahraa Talib Kadhim; Thjeel Al-ogaili; Hanan Abd Ali (Genius Journals, 2023)
In this study, nanoparticles for nickel-tin oxide films were prepared using the sol-gel chemical method. Nanocomposite structural and optical properties were studied. X-ray diffraction measurements showed (SnO2: NiO) (SnO2 NPs). And the structure was validated to crystallize SnO NPs into hexagonal structure with an average crystal size of 13.80 mm. FE-SEM image study showed the surface morphology of SnO2: NiO deposition of SnO2 on a glass substrate. The grain size values for SnO2 and NiO.SnO2 NPs range (24 nm and 38.8 μm), respectively. Energy dispersive X-ray spectroscopy (EDS) was analyzed. The amount of nickel tin with oxygen for a sample prepared at room temperature is less than for other samples prepared. These results are consistent with X-ray diffraction analysis, and FE-SEM FT-IR spectroscopy of the as-synthesized NiO NPs, in the wavelength range from 500 to 4500 cm, showed the FI-IR spectrum of the assynthesized NiO. A broad absorption band is observed at 684.78 cm-1 which is attributed to the Ni–O stretching vibration. The broad peak at 3848.58 cm corresponds to OH. The peaks at 3419.27 and 1637.19 cm were symmetric and asymmetric 0-C-O stretching vibrations of the adsorbed carbonate anion, respectively. The peaks at 680.97 and 1637.57 cm-1 are attributed to Sn-O-H expansion caused by impurities of SnO NPs. peak wavelength range (225-550) nm and an increase in the absorption band towards the red wavelength was observed after the addition of nickel oxide. This phenomenon is called the mean value shift. UV-IR analysis showed the band gap energy value (NiO NPs 3.7ew) (SnO2 NPs 3.3ev) and the band gap value (SnO2: NiO 3.5ev)
Keywords: NanocompositeNiO; SnO2